STEREOTIP SUKU BUGIS DALAM PERSFEKTIF SEJARAH - Nelmawarni (Fakultas Adab dan Humaniora UIN Imam Bonjol Padang, 2022)
Since centuries ago, the Bugis tribe is known as trader, sailor, and immigrants. The excellence of the Bugis trader in mastering the trading network at the Malay Indonesia-Island has been recorded in colonial documents. It causes sailing, trading, and migrating have been identical to the Bugis tribe. However, in the recent decades, there has been stereotypes against Bugis people in Melayu as a pirates. The stereotype had alluded the sensitivity of the Bugis tribe also tarnish the dignity and the identity of the Bugis that causes social turmoil in the form of sense and protests from the Bugis community unity in Malay to the relevant parties. This writing aims to examine and analyze the cause of stereotypical emergence of the Bugis tribe as pirates from point of view of historical. Historical approach was used in this writing, by gathering and analyzing historical sources related to the stereotypes against Bugis in the past. Based on the existing sources of history, it found that the stereotype against the Bugis tribe as traders, sailors, and immigrants had heroism, honesty, discretion, and bravery in their identity. That is the symbol giving to the Bugis tribe's personality at Malacca Strain, it is not proven as pirates.